PENAMPILAN PRODUKSI TERNAK BABI GROWER YANG MENGGUNAKAN TEPUNG KULIT KOPI SEBAGAI BAHAN PENGGANTI SEBAGIAN DEDAK HALUS PADA PAKAN - Timbulus, Mardo C.; Montong, Petrus R.R.I; Mirah, Arie Dp.; Siswosubroto, S.E. (Universitas Sam Ratulangi, 2017)
GROWER PRODUCTION PERFORMANCE USE FLOUR COFFEE PULP AS SUBSTITUTION MATERIALS TO A PARTS OF FINE BRAN ON FEED. Various feed ingredients or waste that have not been utilized for example the skin of coffee fruit can be an alternative feed ingredient source of crude fiber see its content in the skin of the fruit coffee is 33.60%. North Sulawesi, especially Bolaang Mogondow, which is a center of coffee plantation, has a plantation area of 4,097.7 ha, with coffee production reaching 2,135.46 tons of raw material which has not been separated between coffee fruit with its leaves and stems. After the separated coffee fruit obtained as much as 1,288.22 tons per year. Coffee fruit is processed to separate between the seeds and skin after separated obtained by the skin of coffee fruit as much as 448,449 tons. The appearance of production by looking at weight gain, the amount of consumption and the efficiency of feed use is part of the requirement to see the production capability of pigs. The study was conducted for 66 days consisting of 52 days of data collection period and 2 weeks preliminary collecting data aims to determine the effect of coffee skin use as a substitute of some fine bran on the production performance of the grower pigs to the finisher. The study used 16 male and female pigs grower period aged 12-16 weeks descent kinds Yorkshire and Landrace. Randomized block design with four levels of treatment that is 0, 25%, 50%, 75% coffee pulp as a partial replacement of fine bran in 4 groups. Differences in body weight is a replication of the study. The result of analysis of variance (ANOVA) showed that the powder of coffee husk as substitute of bran to the weight gain gave real effect (P <0.05), the amount of feed consumption did not give real effect (P> 0.05) Feed gave a real effect. The result is the use of coffee leaf powder as a substitute of some fine bran in grower pigs until finisher can provide good growth and efficient use of good feed.Keywords: Phase grower, finisher, flour coffee skin